2020
DOI: 10.7150/ijms.46698
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA ZEB1-AS1 acts as a Sponge of miR-141-3p to Inhibit Cell Proliferation in Colorectal Cancer

Abstract: Evidence shows that long noncoding RNAs (lncRNAs) play key roles in various cancers, including colorectal cancer. In this current study, we found that the expression of ZEB1-AS1 in colorectal cancer tissues and cell lines was significantly upregulated, and positively correlated with advanced stage of colorectal cancer. Kaplan-Meier assays also indicated that the expression of ZEB1-AS1 was correlated with poor prognosis in patients with colorectal cancer. Knocking down of ZEB1-AS1 inhibited the proliferation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Siena confirmed that lncRNA ZEB1-AS1 can influence the invasiveness and phenotypic transformation of melanoma through epithelial to mesenchymal transition (EMT) ( Siena et al, 2019 ). Wu believes that ZEB1-AS1 may fuel the profitability of colorectal cancer cells by saponifying miR-141-3p ( Wu et al, 2020 ). LncRNA LINC00997 has been discovered to perform a regulatory role in tumours in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Siena confirmed that lncRNA ZEB1-AS1 can influence the invasiveness and phenotypic transformation of melanoma through epithelial to mesenchymal transition (EMT) ( Siena et al, 2019 ). Wu believes that ZEB1-AS1 may fuel the profitability of colorectal cancer cells by saponifying miR-141-3p ( Wu et al, 2020 ). LncRNA LINC00997 has been discovered to perform a regulatory role in tumours in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…ZEB1-AS1 is an antisense transcript originating from the promoter of Zinc finger E-box binding homeobox 1(ZEB1), a prominent factor in the EMT process of tumor epithelial cells ( Li et al, 2016 ; Caramel et al, 2018 ). ZEB1-AS1 plays a carcinogenic factor in various digestive system tumors, for instance, hepatocellular carcinoma, esophageal cancer, colorectal cancer, and gastric cancer ( Li et al, 2016 ; Zhang et al, 2018b ; Zhao et al, 2019 ; Wu et al, 2020 ). Jiang et al (2020a) proved that ZEB1-AS1 was overexpressed in CCA and promoted CCA growth along with metastasis in vivo , as well as in vitro experiments.…”
Section: Lncrnas As Diagnostic and Prognostic Biomarkers In Cholangio...mentioning
confidence: 99%
“…Lowered miR-200a and elevated miR-200b in serum show similar patterns of being correlated with poor outcomes in CRC patients [89,211]. Moreover, the effectiveness of the carcinogenic influence of each member of the miR-200 family can potentially be mitigated by other ncRNAs that competitively inhibit their actions through sponging [217][218][219][220]. As in the case of other miRNAs and CRC, the basic presence or absence of miR-200 family transcripts in the biofluids of CRC patients alone is not enough to be diagnostic and must be considered within a cellular and histological framework while also considering expression levels of other contextually relevant and impactful ncRNAs.…”
Section: Mir-200 Familymentioning
confidence: 96%